Urea fertilizer: The global challenges and their impact to our sustainability - Yahya, N. (Springer Verlag, 2018)
The world population will increase up to approximately 9.7 billion in 2050. This calls for an attention due to the potential global warming which then leads to an extreme climate change. Svante August Arrhenius has addressed this issue and had predicted global warming in 1896. One of the gases that contributes toward the global warming is N2O which is due to the fertilizer effect, mainly urea. The production of urea by using conventional fertilizer plant has its impact on environment and certainly economy. The production of the fertilizers has great impact on the profitability due to its greenhouse gas intensive nature and climate policies. It was found that 1 ton of N2O is equivalent to 298 tons of CO2, and it has an atmospheric lifetime of 110Â years. Nitrous oxide and nitric oxide emission have been increased steadily which ultimately increases the global warming potential. Considering the adverse effects of conventional fertilizers, the Green Urea is proposed as new nitrogen-based enhanced efficiency fertilizer (EEF) production and utilization, where a novel integrated ammoniaâurea process and product was proposed. Â© 2018, Springer Nature Singapore Pte Ltd.